Niat Keberlanjutan Penggunaan Aplikasi myIM3 pada Generasi Z di Solo Raya - Hasna Asih Namiroh; Novel Idris Abas (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This study aims to analyze the influence of promotion offers, perceived utility, personalization, and social support on hedonic value and continuance intention in using the myIM3 application. The subjects of this research are active users of the myIM3 application. The method used is a quantitative approach was employed through a survey of 250 active users selected using purposive sampling. The research instrument consisted of a questionnaire covering respondent demographics, perceptions of the study variables, hedonic value, and continuance intention. Data were analyzed using Structural Equation Modeling (SEM) with the assistance of SmartPLS software. The results indicate that promotion offers and perceived utility have a significant influence on hedonic value. Furthermore, hedonic value significantly affects continuance intention. However, social support does not show a significant effect on hedonic value, and personalization does not significantly influence continuance intention. This study contributes theoretically by extending the literature on factors influencing hedonic value and continuance intention in the context of mobile application usage, particularly myIM3. Additionally, the findings provide practical implications for myIM3 app developers and marketers in designing more effective strategies to enhance user satisfaction and loyalty.